Problems of Formation and Implementation of the Criminal Law Policy of Counteraction to Terrorism and Armed Aggression - Yu. V. Orlov; S. V. Shchebetun (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article is devoted to the study of the problem of formation and implementation of the criminal law policy of counteraction to terrorism and armed aggression. It identifies, describes and explains the existing contradictions between the logics of peace and war in the dimension of competition between the anti-terrorist and anti-war paradigms. It is proved that they lead to misapplication of the law and violations to the principle of equality for citizens before the law. In addition, the ways of eliminating contradictions are proposed by changing approaches to the qualification of terrorist crimes, taking into account the armed conflict as a contextual element in the composition of relevant socially dangerous acts.